Corporate Risk Culture, Governance and Foreign Exchange Risk Management - Han, Xu (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2025)
This thesis investigates the influence of corporate risk culture and corporate governance on firm-level foreign exchange (FX, hereafter) rate risk management. This thesis adopts a three-essay format to explore how managerial overconfidence, enterprise risk management (ERM) and different types of institutional ownership affect corporate hedging decisions in managing foreign exchange rate risk. Managerial overconfidence indicates the preference of management for risk and uncertainty, while corporate adoption of enterprise risk management exhibits corporate risk appetite in a holistic view. Because corporate risk culture is reflected in displayed managerial risk attitudes (Pan et al., 2016), this thesis utilises managerial overconfidence and ERM adoption to indicate corporate risk culture. This study examines the influence of corporate risk culture, which is reflected at both the managerial level and firm level, and external corporate governance proxied by various institutional ownerships on foreign exchange hedging. In this thesis, I utilise a longitudinal design and include more than 1000 non-financial U.S. companies listed in the S&P 1500 Index. I adopt a novel text-based approach to proxy for foreign exchange financial hedging, which is examined across three essays, by enumerating the occurrences of keywords related to foreign exchange risk financial hedging mentioned in firms' 10-K annual reports with a Python-based crawler program. Chapter 2 presents the first essay which utilises a large panel dataset composed of 14,241 observations from 1,088 non-financial U.S. companies to examine how managerial overconfidence, as one of the proxies for corporate risk culture, influences corporate FX financial hedging. I employ multiple approaches to measure levels of managerial overconfidence, including executive option holding and late-exercising behaviours, net stock purchases, firm-level investment scales and press-based measures. I find that firms with overconfident Chief Executive Officers (CEOs) are more likely to adopt more currency derivatives to hedge against foreign exchange risk. I also supplement empirical evidence to the literature that firms with overconfident Chief Financial Officers (CFOs) tend to hedge more. Moreover, executive characteristics, including age, tenure, duality and educational background, also play a role in affecting levels of FX financial hedging. Chapter 3 examines the influence of the second proxy for corporate risk culture, the adoption of enterprise risk management (ERM) and its components on foreign exchange rate hedging with a longitudinal design of 15,297 non-financial U.S. firm-year observations. The results suggest that firms with more advanced ERM implementation are more likely to adopt currency derivatives to hedge against FX risk. I implement multiple endogeneity tests, including two-stage least-square (2SLS), dynamic panel generalised method of moments (GMM), propensity scores matching and several robustness tests to confirm that such influence is not endogenously determined. Moreover, the empirical results suggest that ERM plays a limited role in low-multinational firms and increases corporate use of currency derivatives in highly multinational and global firms. Furthermore, ERM firms with female or long-tenured CEOs are more likely to conduct FX financial hedging. I also find that ERM firms with CEOs serving as chairmen or having finance-related education tend to use currency derivatives. Chapter 4 examines the impact of various institutional investment styles on target firms' risk management strategies with a large panel data sample consisting of 13,651 observations. I find that institutions targeting undervalued firms (Value-style) are motivated to monitor firms to adopt currency derivatives to mitigate FX risk exposure, while institutions targeting firms with more growth opportunities (Growth-style) have no significant impact on corporate financial hedging. To address endogeneity concerns, I employ a two-stage least squares analysis utilising instrumental variables of mutual fund flow and the firm addition to the Russell 1000 index. I also find evidence that value-style institutions play a consistent monitoring role in foreign currency hedging across target firms with varying sizes. Furthermore, value-style institutional ownership is positively associated with hedging decisions in firms with higher debt financing and capital ratios. However, the relation reverses in companies with greater profitability, higher equity financing, and stronger solvency. Lastly, firms invested by institutions favouring a value investment style, a long-term horizon, and larger targets' firm sizes exhibit lower foreign exchange rate risk exposure.
APPROVED
Keywords: managerial overconfidence; foreign exchange risk; foreign currency hedging; enterprise risk management; institutional investment